Actin depolymerizing factor-based nanomaterials: A novel strategy to enhance E. mitis-specific immunity - Yu, ZhengQing; Xu, LiXin; He, Ke; Lu, MingMin; Yan, RuoFeng; Song, XiaoKai; Li, XiangRui (Frontiers in Immunology, 2022)
The epidemic of avian coccidiosis seriously threatens the animals’ welfare and the economic gains of the poultry industry. Widespread in avian coccidiosis, Eimeria mitis (E. mitis) could obviously impair the production performance of the infected chickens. So far, few effective vaccines targeting E. mitis have been reported, and the nanovaccines composed of nanospheres captured our particular attention. At the present study, we construct two kinds of nanospheres carrying the recombinant E. mitis actin depolymerizing factor (rEmADF), then the characterization was then analyzed. After safety evaluation, the protective efficacy of rEmADF along with its nanospheres were investigated in chickens. The promoted secretions of antibodies and cytokines, as well as the enhanced percentages of CD4+ and CD8+ T cells were evaluated by the ELISA and flow cytometry assay. In addition, the absolute quantitative real-time PCR (qPCR) assay implied that vaccinations with rEmADF-entrapped nanospheres could significantly reduce the replications of E. mitis in feces. Compared with the rEmADF-loaded chitosan (EmADF-CS) nanospheres, the PLGA nanospheres carrying rEmADF (EmADF-PLGA nanosphers) were more effective in up-regulating weight efficiency of animals and generated equally ability in controlling E. mitis burdens in feces, suggesting the PLGA and CS nanospheres loaded with rEmADF were the satisfactory nanovaccines for E. mitis defense. Collectively, nanomaterials may be an effective antigen delivery system that could help recombinant E. mitis actin depolymerizing factor to enhance immunoprotections in chicken against the infections of E. mitis.